Study and Application of Full Tailing Deep Concentration and Rapid Dewatering Technology - Liang Peng; Bokun Zheng; TengLong Huang; Xin Zhu; Yang Liu; Fan Hu (Advances in Civil Engineering)
The problem of unstable full tailing sand concentration and dewatering in some mine filling systems has led to substandard bottom flow concentration of tailing sand concentration equipment, wide fluctuation ranges of filling concentration, substandard return water concentration at filling stations, and high flocculant addition cost. Through flocculation and sedimentation tests, the effect of the flocculant and sedimentation law and the effect of slurry concentration on sedimentation rate were studied, and the field application of the flocculant addition point model was verified. The results showed that (1) when the dose of the flocculant was added, the F1-type polyacrylamide as the flocculant made the best settling effect of the whole tailing sand in the test, as judged by comparing the falling rate of the clarified layer and the clarification degree of the supernatant. (2) With the increasing flocculant concentration, the settling speed of tailing sand gradually becomes slower; the range of the best settling concentration was 8%–18% of tailing sand concentration; and the concentration of tailing sand corresponding to the maximum solid flux was 10%–14%. (3) Relying on the site conditions of a domestic copper mine, the feed concentration was diluted from 20%–25% to 10%–12%, and the overflow water clarification test was less than 300 ppm, which verified the flocculant test and the correctness of the flocculant addition point model. The type and dosage of the flocculant as well as the feed concentration of the tailing slurry all have an effect on the flocculation and settling effect. The results of the study can provide some implications for the efficient flocculation and settlement of tailings in other mines.